Analisis Kegiatan Pembelajaran Pendidikan Jasmani di SD 060877 Medan Perjuangan - Siregar, Hanif Luthfi; Maya, Mutiah Dina; Rif’an, Muhammad; Asmon, Shaqilla Rizky Dewi; Fadilah, Rizki; Siregar, Fajar Sidik (Indo-MathEdu Intellectuals Journal, 2024)
This research discusses the implementation of physical education, sports, and health (PJOK) in the State Elementary School (SD) 060877 Medan. This study found several shortcomings in the implementation of PJOK in elementary schools, including the lack of variety of learning methods, lack of use of learning media, lack of student involvement, and lack of authentic assessment. This study uses a qualitative approach through a descriptive method. The data collection technique in this study is interview observation. The data collection technique in this study is interview observation. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. Based on the results of the research, a variety of learning methods are needed, utilizing learning media, increasing student involvement, and carrying out authentic assessments to improve the quality of PJOK learning. Through these improvements, the implementation of PJOK in elementary schools can become more effective and efficient and help achieve national education goals which include the development of motor skills, abilities, physical, knowledge, sportsmanship, habituation of a healthy lifestyle, and character formation